Hubungan Pola Pemberian Makan dan Tingkat Pengetahuan Ibu dengan Kejadian Stunting pada Anak Balita di Kelurahan Jagir Surabaya - Andi Batari Khairunnisa (Media Gizi Kesmas, 2023)
Background: Stunting is defined as a state of malnutrition characterized by a stunted body shape in terms of body length index for age (LAZ) or height for age (HAZ). An essential factor in the development of children under five is the food-related problem, because food contains nutrition. Objectives: This study aimed to determine the relationship between dietary habits and maternal knowledge level in disabled children under five years of age in Jagiri village, Surabaya. Methods: This study used observational quantitative research with descriptive-analytic method with a cross-sectional study design. Samples were taken using a proportional random sampling technique on 79 children under five. Results: There was a correlation between diet and species growth (p = 0.000), there was a link between an abundance-based diet and leanness (p = 0.000), there was a correlation between program feeding practices and physical growth (p = 0.000), there was a correlation between feeding patterns (total) and stunting in children under five (p=0.000), and there was a correlation between mother's knowledge level and physical maturity (p=0.000). Conclusions: There was a significant association between maternal knowledge of under-5 child nutrition practices and stunted growth in the Jagir Village, Surabaya. This was because a long-term diet inconsistent with the nutritional needs of children under five can lead to chronic nutritional problems such as stunting. A lack of mothers' knowledge about nutrition and growth in nursing can lead to stunted growth of children under five.